Prediction of prognosis, immune infiltration, and personalized treatment of hepatocellular carcinoma by analysis of cuproptosis-related long noncoding RNAs and verification in vitro - Li, Shanbao; Zhu, Zhonglin; Lu, Jing; Cao, Wanyue; Song, Fangbin; Xiao, Cao; Zhang, Peng; He, Zeping; Weng, Junyong; Xu, Junming (Frontiers in Oncology, 2023)
Background：The correlations between the cuproptosis and long noncoding RNAs (lncRNAs) with the tumor microenvironment (TME), immunotherapy, and some other characteristics of hepatocellular carcinoma (HCC) remain unclear. Results: A CRLncSig prognostic risk model with good predictive ability was constructed. The low-risk group had a longer overall survival (OS), lower tumor purity, more extensive immune cell infiltration, higher immune score, enrichment in immuneactivated pathways, and more positive response to immunotherapy versus the high-risk group. CRGC-B exhibited best OS and lowest tumor stage; the immune cell infiltration analysis was similar to the low-risk group in CRLncSig. CRGC-B belonged to the "immune-high" group of the TME. The low-risk group had a higher TIDE score and susceptibility to anti-tumor drugs. The lncRNA AL158166.1 had the highest hazard ratio. The levels of AL158166.1 were higher in HCC tissues versus healthy tissues. Knockdown of AL158166.1 could lead to a increase in intracellular Cu concentration, induce the DLAT low expression, and inhibit the proliferation and migration of HCC cells, whereas overexpression of AL158166.1 exerted the reverse effect. Conclusions: Overall, a new CRLncSig prognostic risk model and a cuproptosisrelated molecular signature were constructed and evaluated. The model and signature were associated with the prognosis, immune infiltration, and immunotherapy of HCC.Inhibiting the lncRNA AL158166.1 may induce cuproptosis and showed potential for the inhibition of tumors. Evaluation of the CRLnc, CRLncSig, and CRGC may enhance our understanding of the TME, determine the effectiveness of immunotherapy, and act as a marker for the prognosis of HCC.